Effect of Microbial Phytase in Soybean Meal Based Broiler Diets Containing Low Phosphorous - Mondal, M.K.; Panda, S.; Biswas, P. (International Journal of Poultry Science, 2007)
A six wk feeding experiment was conducted with d-old four hundred broiler chicks (Ven Cobb) to determine the effects of microbial phytase (Allzyme) supplementation in soybean meal based broiler diet containing low phosphorous. These birds were randomly divided into four dietary treatment groups of 100 broilers each. Each treatment group was further sub-divided into five replicates of 25 broilers per replicate. The treatments groups were control; low phosphorus; low phosphorus plus 250 PU phytase/kg diet; low phosphorus plus 500 PU phytase/kg diet. There were significant effects of dietary treatments on body weight, body weight gain, feed intake and feed conversion ratio at 0 to 42 days. The body weight and the body weight gain of the broilers fed the control and low phosphorus plus phytase diet were heavier (p<0.05) than other treatment. Feed conversion ratio of broiler fed on low phosphorus plus phytase 500 PU/kg was significantly better (p<0.05) than that of broilers fed on low phosphorus phytase supplementation had no effect on broiler mortality. Concentration of blood metabolites were unaffected (p>0.05) by the dietary treatments. Supplemental phytase (500 PU/kg) maintained the same plasma concentration of Ca and P as found in control whereas the concentration of Fe. Mn and Zn was unaffected by the dietary treatments. The percentage of tibia ash, Ca and phosphorus and retention of Ca and P was significantly increased by the addition of microbial phytase to low phosphorus diet. This study demonstrates that microbial phytase can compensate the untoward effect of low phosphorus levels in the soybean meal based broiler diet.